Photobiomodulation therapy approach to a rare phenomenon of radiation recall reaction triggered by cisplatin in a cervical cancer patient: a case report and scoping review - Gomes, Paloma; Abreu, Wenzel Castro de; Reis, Ricardo Gomes dos; Guerra, Eliete Neves Silva; Ferreira, Elaine Barros; Reis, Paula Elaine Diniz dos (Frontiers in Oncology, 2026)
PurposeRadiation recall reaction (RRR) is a rare and poorly understood phenomenon of tissue radiotoxicity. It is typically triggered by exposure to certain agents, most commonly cytotoxic drugs such as cisplatin. We conducted a scoping review following the methodology proposed by the JBI collaboration and PRISMA-ScR extension. It aimed to map the evidence concerning the treatment of RRR triggered by cisplatin.MethodsSearches were performed in PubMed/MEDLINE, EMBASE, Web of Science Core Collection, Cochrane Database, and ProQuest™ on March 9, 2025. Eligible studies included primary research, guidelines, and study protocols that addressed RRR as a primary or secondary outcome. A case report was also described.ResultsEight studies were included, and the main treatments for RRR were topical steroids and antihistamines. A 36-year-old woman with cervical cancer developed intense hyperpigmentation in the inguinal, vulvar, and anal areas, along with anal and labial fissures, dry desquamation in the inguinal region, and vaginal stenosis, 3 days after cisplatin. The diagnosis was RRR affecting mucosa and skin in the intimate region. Photobiomodulation therapy (PBMT) was initiated using lasers emitting wavelengths of 660 and 808 nm for tissue repair in the vulva, anus, and groin, and LEDs emitting 450 nm for vaginal stenosis and 590 nm for hyperpigmentation. Following the first PBMT session, the patient showed an excellent clinical response after 1 week, with a significant reduction in the severity of RRR.ConclusionPBMT appears to be a viable, non-invasive, and low-cost treatment option for RRR, with no reported side effects.